ГЕНДЕРНЫЕ РАЗЛИЧИЯ КОГНИТИВНЫХ ФУНКЦИЙ ПРИ ЦЕРЕБРОВАСКУЛЯРНОЙ ПАТОЛОГИИ (World Science, 2018)
Clinical, instrumental and neuropsychological examination was carried out in 110 patients with chronic brain ischemia of the 2nd degree on the background of hypertension of the 2nd stage. The subjects were divided into 2 groups based on gender. Signs of venous cerebral dishelie valley significantly more cases in the group of women. It is shown that the group of women with cerebral venous Disgaea more patients had cognitive impairment (MMSE scale). Also, the low rate of induced cognitive potentials in the brain (the method of cognitive evoked potentials) was more pronounced in women than in men. It should be assumed that in hypertensive disease, the presence of concomitant cerebral venous dysfunction aggravates the course of cerebral ischemia, especially in women.